Development and Preliminary Validation of the Active Citizen Compass Questionnaire: The Dutch–Flemish and Greek Versions - Chiou, Vana; Holz, Oliver (Revija za elementarno izobraževanje, 2025)
This study aimed to develop a questionnaire for assessing teachers’ practices, teaching knowledge, and school practices related to active citizenship in a cross-national study. The first draft of the Active Citizen Compass (ACC) questionnaire in English was examined by an expert panel. The questionnaire was translated into Dutch and Greek, and tested for ambiguity, clarity, and user friendliness. Thereafter, the Dutch-Flemish and Greek versions were pilot tested on 54 teachers from Flanders and 63 teachers from Greece. Reliability and validity evidence indicates the ACC scales in Dutch and Greek are a reliable and valid measure of active citizenship in schools.
Keywords: active citizenship; questionnaire; validation; teachers; schools.